Evaluasi Pengelolaan Limbah Bahan Berbahaya dan Beracun di PT. X Industri Plastik - Mila Dirgawati; Aulya Amitasyah (Jurnal Serambi Engineering, 2024)
PT X is one of the companies that generates hazardous waste from production and non-production activities. There are nine types of B3 waste generated, namely used oil, electronic waste, used batteries /feet, B3 contaminated mop, used B3 packaging, used refrigerant from electronic equipment, expiredproducts / raw materials, materials / products that do not meet technical specifications and productionresidues. The purpose of the study is to determine the source, suitability of B3 waste management carriedout by PT X and provide recommendations for improvement of non-compliant findings. This researchuses primary data collection methods and secondary data. The results showed the percentage of theoverall level of suitability of B3 waste management carried out by PT X obtained a value of 68.1% whichmeans it is included in the "good" category. Recommendations for improvement that can be given are thatthe packaging needs to be given a symbol that matches its characteristics and a label on each hazardouswaste packaging found at PT. X and using closed conveyance so that it can load category 1 and category2 B3 waste simultaneously by considering the compatibility of B3 waste.